2017
DOI: 10.1177/1745499917711543
|View full text |Cite
|
Sign up to set email alerts
|

More or less engaged in doctoral studies? Domestic and international students’ satisfaction and motivation for doctoral studies in Finland

Abstract: This study examines whether students who started their doctoral degree with different motivation profiles differ in their emotional engagement in their studies, and how this pattern differs between domestic and international students in Finland. This study used survey data collected from 1064 domestic and 120 international students. The results showed that students who started their degree with a low motivation to extend their career prospects were significantly less satisfied with their studies. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
1
11
0
1
Order By: Relevance
“…Our study provides further support of the importance of a match between the doctoral program and students’ goals, and, moreover, we find that this alignment may be particularly important for students who travel a great distance both geographically and culturally to pursue their doctorate. Our results relate to a prior study of over 1,100 students studying at the University of Helsinki that found that international students are more motivated by their career goals to pursue a doctoral program as compared to domestic students (Sakurai et al , 2017). While mismatch of interest and/or goals was mentioned less often among international students in the natural and biological sciences, they expressed concern about career preparation, which is related to their occupational goals.…”
Section: Discussionsupporting
confidence: 77%
“…Our study provides further support of the importance of a match between the doctoral program and students’ goals, and, moreover, we find that this alignment may be particularly important for students who travel a great distance both geographically and culturally to pursue their doctorate. Our results relate to a prior study of over 1,100 students studying at the University of Helsinki that found that international students are more motivated by their career goals to pursue a doctoral program as compared to domestic students (Sakurai et al , 2017). While mismatch of interest and/or goals was mentioned less often among international students in the natural and biological sciences, they expressed concern about career preparation, which is related to their occupational goals.…”
Section: Discussionsupporting
confidence: 77%
“…For example, almost one-third (31%) of the doctoral students pointed out that their motive for pursuing a doctoral degree was to improve their career prospects (Neves, 2018). Accordingly, instrumental motives for undertaking doctoral studies, such as getting a better salary or promotions once the degree is completed are also employed (Guerin et al, 2015;Sakurai et al, 2017;Stubb et al, 2012).…”
Section: Interest In Doctoral Studiesmentioning
confidence: 99%
“…Regarding motivation for studies, Chue and Nie (2016) found that international students in Singapore had higher levels of self-determined motivation, in comparison to domestic students. A study of doctoral students in Finland found that the international students were more motivated and satisfied than their Finnish counterparts (Sakurai et al, 2017). A comparison of international and domestic students in the United States shows that international students score slightly higher on some aspects of engagement, while U.S. students rated their educational experience slightly higher (Korobova & Starobin, 2015).…”
Section: Earlier Researchmentioning
confidence: 99%
“…Some studies have addressed differences in social background, finding that internationally mobile students more often are of higher social origin (e.g., Findlay et al, 2012;Gerhards & Hans, 2013), and a few comparisons of motivation and personal features exist. Research investigating motivation among internationally mobile vs. nonmobile students indicates a higher level of motivation among those with mobility experience (Chue & Nie, 2016;Sakurai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%